Unraveling protein repulsion forces with nanocelluloses: insights from force spectroscopy - Li, Jing (European physical journal. Applied physics, 2025)
Despite the promising potential of novel surface-functionalized nanocelluloses in advanced technology applications, mechanisms of nanoscaled interacting forces and their origins during interactions between proteins and these materials in biologically relevant environments remain poorly understood. This study explores force interactions between bovine serum albumin (BSA) and three functionalized nanocelluloses, OSO₃⁻-modified CNCs, lignin-residual CNCs (LCNCs), and COO⁻-modified TEMPO-oxidized cellulose nanofibers (TCNFs), to understand protein-nanocellulose interactions using Peakforce quantitative nanomechanical mapping in salt solution at two pH values. The force spectroscopy measured by a protein colloidal probe revealed that TCNFs and LCNCs resist BSA adsorption via pH-dependent repulsion, independent of substrate and protein charge. At pH 3.5, TCNFs showed short-range repulsion (25 nm) against oppositely charged proteins, decreasing to separation distance of 14 nm at pH 7.2. The secondary minima observed at pH 7.2 confirmed the electrostatic-dominant repulsive behavior of TCNFs. LCNCs displayed steric repulsion (13 nm) at pH 3.5 and very long-ranged repulsion (75 nm) at pH 7.2. These repulsion mechanisms, driven by electro-steric repulsion, and hydration forces resulting from formation of a water layer bound to proteins during protein layer compression, deviate from classical DLVO theory. The proposed interaction force mechanisms for protein repulsion were further validated by energy dissipation data and dynamic contact angle experiments. The results showed that TCNFs formed compact layers preserving protein conformation, facilitated by the surface chemical and structural advantages of TEMPO-oxidized TCNFs. While the lignins on LCNCs created flat LCNC-BSA complex layers influenced by lignin chemistry. The findings highlight the importance of optimizing nanocellulose surface chemical properties to enhance protein repellency while maintaining mechanical strength in biological systems.